Non‐contrast myocardial infarct scar assessment using a hybrid native T1 and magnetization transfer imaging sequence at 1.5T. Issue 5 (18th December 2018) - Duan, Chong; Zhu, Yanjie; Jang, Jihye; Rodriguez, Jennifer; Neisius, Ulf; Fahmy, Ahmed S.; Nezafat, Reza
Abstract : Purpose: To develop a gadolinium‐free cardiac MR technique that simultaneously exploits native T1 and magnetization transfer (MT) contrast for the imaging of myocardial infarction. Methods: A novel hybrid T one and magnetization transfer (HYTOM) method was developed based on the modified look‐locker inversion recovery (MOLLI) sequence, with a train of MT‐prep pulses placed before the balanced SSFP (bSSFP) readout pulses. Numerical simulations, based on Bloch‐McConnell equations, were performed to investigate the effects of MT induced by (1) the bSSFP readout pulses, and (2) the MT‐prep pulses, on the measured, "apparent, " native T1 values. The HYTOM method was then tested on 8 healthy adult subjects, 6 patients, and a swine with prior myocardial infarction (MI). The resulting imaging contrast between normal myocardium and infarcted tissues was compared with that of MOLLI. Late gadolinium enhancement (LGE) images were also obtained for infarct assessment in patients and swine. Results: Numerical simulation and in vivo studies in healthy volunteers demonstrated that MT effects, resulting from on‐resonance bSSFP excitation pulses and off‐resonance MT‐prep pulses, reduce the measured T1 in both MOLLI and HTYOM. In vivo studies in patients and swine showed that the HYTOM sequence can identify locations of MI, as seen on LGE. Furthermore, the HYTOM method yields higher myocardium‐to‐scar contrast than MOLLI (contrast‐to‐noise ratio: 7.33 ± 1.67 vs. 3.77 ± 0.66, P < 0.01). Conclusion: The proposed HYTOM method simultaneously exploits native T1 and MT contrast and significantly boosts the imaging contrast for myocardial infarction.